Preparation method of biological porous zinc alloy with composite structure for orthopedics implantation

Through laser additive manufacturing and vacuum-gas phase dealloyment process, bioporous zinc alloys with macro-microscopic double-scale composite pore structures are prepared, which solves the problems of mechanical properties, modulus regulation and biological activity improvement of porous zinc alloys in the prior art. , achieving good adhesion and differentiation of osteocytes, avoiding the problem of biocoating shedding.

CN119457122APending Publication Date: 2025-02-18NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411597063.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

Smart Images

  • Figure CN119457122A_ABST
    Figure CN119457122A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biological porous zinc alloy with a composite structure implanted in the orthopedics department, which comprises the following steps: firstly, carrying out optimization design modeling by utilizing a computer pore structure, preparing a porous zinc alloy with a macroscopic pore structure by adopting a selective laser melting process according to a modeling result, and then preparing a micro-nano pore structure by adopting a vacuum-gas phase dealloying process. And obtaining the biological porous zinc alloy with the composite structure. On the basis of laser additive manufacturing and a vacuum-gas phase dealloying process, the biological porous zinc alloy with the macro-micro double-scale composite pore structure is obtained, the structures of macro pores and micro pores can be adjusted by adjusting process parameters, the mechanical property and modulus regulation and control of the porous zinc alloy are met, and meanwhile the mechanical property of the porous zinc alloy is improved. And the biological activity of the porous zinc alloy is effectively improved, adhesion, growth and differentiation of bone cells are well promoted, personalized pore structure optimization design and preparation are achieved, and the porous zinc alloy is suitable for orthopedic implant materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser additive manufacturing and vacuum vapor dealloying, and in particular relates to a method for preparing a biological porous zinc alloy with an orthopedic implant composite structure. Background Art

[0002] Clinically, bone defects larger than 6mm are defined as large bone defects, and their non-union rate exceeds 80%. Generally speaking, in clinical treatment of large bone defects, hard tissue replacement techniques are often used, and the core is the design and manufacture of hard tissue implants. Medical degradable metal materials represented by magnesium, iron, zinc and their alloys can obtain an elastic modulus that matches human bone tissue through porous structure design, and can be gradually degraded in the human body, which not only effectively avoids the problem of osteoporosis caused by stress shielding, but also avoids the cost and risk of secondary surgery. Therefore, it has attracted widespread attention from researchers in the field of orthopedics.

[0003] Zinc is one of the essential trace elements for the human body and an important nutrient. More than 100 enzymes in the human body contain zinc. They are widely involved in the synthesis and decomposition of important life substances such as carbohydrates, lipids, proteins and nucleic acids in the body. They play an extremely important role in the growth and development of the human body and play an important role in the maintenance of the body's health. In vitro studies have shown that zinc is a key element in the body's bone formation ability and plays a significant role in the body's physiological functions, cell metabolism and gene expression. In addition, the corrosion rate of zinc as a biomedical material is just between Mg and Fe, which avoids the degradation rate problem that exists in the current research of magnesium alloys and iron alloys. Therefore, moderate corrosion behavior and excellent mechanical properties provide zinc alloys with potential prospects as tissue engineering scaffolds, and the preparation of porous zinc alloy patches for bone repair has also become a hot topic of research.

[0004] In terms of macroscopic pore structure, invention patent CN108977682A specifically discloses a method for preparing a porous zinc-silver alloy bioscaffold. This method first melts the zinc-silver alloy, then puts a sodium chloride pore-forming agent into a cylindrical stainless steel mold with a hole at the bottom, pre-treats the pore-forming agent by heating, and then pours the molten zinc-silver alloy melt into the stainless steel mold pre-treated with sodium chloride. Finally, the lid is quickly closed, and compressed gas is introduced to obtain a porous zinc alloy containing sodium chloride. Ultrasonic cleaning is used to remove sodium chloride to obtain the required porous zinc. This method can achieve the regulation of pore structure by selecting and pre-treating sodium chloride particles, thereby obtaining a modulus that matches bone tissue, but it does not further improve the biological activity of the zinc alloy from a structural perspective, and it is necessary to additionally design a bioactive coating to promote the application of porous zinc alloys.

[0005] In terms of microscopic pore structure, invention patent CN109811396A specifically discloses a method for preparing nano-porous zinc. The method first obtains a zinc-magnesium alloy by alloy smelting, and then removes the magnesium element in the zinc-magnesium alloy by electrochemical corrosion, thereby forming a nano-porous zinc skeleton with interconnected structures. At the same time, the application of nano-porous zinc in the field of antibacterial is provided. The nano-scale interconnected pore structure constructed by this method can effectively improve the biological activity of zinc alloys, but it cannot achieve effective regulation of the modulus and mechanical properties of porous zinc.

[0006] For the above reasons, the invention patent CN113633831A is based on the idea of ​​alloy smelting and air pressure infiltration casting, first prepares a porous zinc alloy, then the porous zinc after cutting is acid treated, and finally the porous zinc alloy after treatment is immersed in a polymer (sodium alginate, pectin, chitosan, etc.) solution, centrifugal drying. Obtaining a porous zinc alloy bone tissue engineering scaffold with high porosity, adjustable pore size, higher strength, and better biological activity. This method, on the basis of the invention patent CN108977682A, prepares an activation coating of zinc alloy, which can effectively promote the application of porous zinc alloy in the field of bone tissue repair. However, the process of this method is complicated, and the bonding between the prepared coating and the substrate is poor, and it is easy to fall off during application and cannot meet the use requirements. To solve the above problems, invention patent CN117564274A discloses a method for preparing a porous zinc alloy with a composite structure based on metal smelting and vacuum infiltration casting technology. Microporous pore-forming agent TiH2 is added during the smelting process, and then a macro-micro composite porous structure porous zinc alloy is simultaneously formed during the infiltration process. The method has a simple process and can effectively solve the problem of easy shedding of the bioactive coating on the surface of the porous zinc alloy. However, the macroscopic pore structure prepared by the infiltration casting process depends on the shape and size of the pore-forming agent, and cannot achieve personalized pore structure optimization design and preparation.

[0007] In addition, invention patents CN113770352A and CN107855528A disclose methods for preparing bioporous zinc based on powder metallurgy routes; invention patent CN115671380A discloses a method for preparing porous zinc alloys by combining 3D printing and reverse replication casting. These invention patents have enriched and developed the preparation methods of medical porous zinc alloys, but none of them can simultaneously achieve effective regulation of the mechanical properties, modulus and biological activity of porous zinc alloys. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a method for preparing a composite structure biological porous zinc alloy for orthopedic implants in view of the deficiencies of the above-mentioned prior art. The method is based on laser additive manufacturing and vacuum-gas phase dealloying process to obtain a biological porous zinc alloy with a macro-micro dual-scale composite pore structure. While satisfying the mechanical properties and modulus regulation of the porous zinc alloy, it effectively improves the biological activity of the porous zinc alloy, promotes the adhesion, growth and differentiation of bone cells, and solves the current problem that porous implants need additional coating preparation and the current situation that the bonding strength between the coating and the substrate is poor and easy to fall off.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a composite structure biological porous zinc alloy for orthopedic implants, characterized in that a computer pore structure optimization design model is first used, and a laser selective melting process is used to prepare a porous zinc alloy with a macroscopic pore structure according to the modeling results, and then a vacuum-vapor phase dealloying process is used to prepare a micro-nano pore structure to obtain a composite structure biological porous zinc alloy.

[0010] The above-mentioned method for preparing a composite structure bioporous zinc alloy for orthopedic implants is characterized in that the computer pore structure optimization design modeling is performed based on the design criteria of bone implants. Generally, in implant research, matching the mechanical properties of human bone tissue, having a structure similar to human bone tissue, and having good biocompatibility are used as the design criteria for bone implants.

[0011] The above-mentioned method for preparing a composite structure bioporous zinc alloy for orthopedic implants is characterized in that the raw material powder used in the laser selective melting process is spherical powder for 3D printing, with a particle size of 15μm to 53μm, and the raw material powder is mechanically mixed under a vacuum state.

[0012] The above-mentioned method for preparing a composite structure bioporous zinc alloy for orthopedic implants is characterized in that the parameters of the laser selective melting process are: laser power 60W to 120W, scanning speed 200mm / s to 800mm / s, and the scanning strategy is strip mode. The parameters of the laser selective melting process match the melting point and forming characteristics of the zinc alloy, so the forming performance within this process range is better.

[0013] The above-mentioned method for preparing a composite structure bioporous zinc alloy for orthopedic implants is characterized in that the parameters of the vacuum-gas phase dealloying process are: vacuum degree less than 10Pa, dealloying temperature 450°C to 650°C, and dealloying time 1h to 3h.

[0014] The above-mentioned method for preparing a bioporous zinc alloy with a composite structure for orthopedic implants is characterized in that the method comprises the following steps:

[0015] Step 1: Select 3D printed spherical zinc powder and titanium powder or iron powder in a mass ratio of 30-70:70-30 and mechanically mix them on a double-shaft horizontal mixer. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;

[0016] Step 2: Based on the design criteria of bone implants, computer modeling software is used to optimize the macroscopic pore structure, and a porous zinc alloy model of TPMS, body-centered cubic or negative Poisson's ratio structure is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 60% to 90%;

[0017] Step 3: Using the mixed powder obtained in step 1 as a raw material, according to the modeling result in step 2, a porous zinc alloy with a macroscopic pore structure is prepared by a laser selective melting process; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 60W-120W, scanning speed 200mm / s-800mm / s, and the scanning strategy is strip mode;

[0018] Step 4: subjecting the porous zinc alloy with a macroporous structure prepared in step 3 to low-temperature sintering and high-temperature-gas phase dealloying treatment, taking it out after cooling in the furnace, ultrasonically cleaning it with anhydrous ethanol for 30 minutes and then drying it to obtain a composite structure biological porous zinc alloy; the temperature of the low-temperature sintering is 250°C to 300°C, and the time is 30 minutes; the temperature of the high-temperature-gas phase dealloying is 450°C to 650°C, the vacuum degree is 5.5Pa, and the time is 1h to 3h.

[0019] The present invention uses zinc powder and titanium powder or iron powder as raw materials, first mechanically mixes to obtain physically doped mixed powder as zinc alloy powder raw material, and simultaneously adopts computer modeling software to construct a macroscopic pore structure, and then adopts a laser selective melting process to prepare a porous zinc alloy with a macroscopic pore structure, and then according to the evaporation characteristics of zinc under a vacuum state, low-temperature sintering and high-temperature-gas phase dealloying are carried out in a vacuum furnace to prepare a composite structure porous zinc alloy with a micro-nano pore structure on the surface.

[0020] The above method is characterized in that the parameters of the laser selective melting process in step three are: laser power 80W, scanning speed 400mm / s, or laser power 120W, scanning speed 600mm / s.

[0021] The above method is characterized in that the temperature of the low-temperature sintering in step 4 is 300°C and the time is 30 minutes; the temperature of the high-temperature-gas phase dealloying is 550°C and the time is 2 hours.

[0022] The above method is characterized in that the composite structure biological porous zinc alloy in step 4 has both micro-macro pore structure characteristics. This structural feature can not only effectively adjust the modulus and mechanical properties of the porous zinc alloy, but also improve the biological activity of the porous zinc alloy, and can well promote the adhesion, growth and differentiation of bone cells.

[0023] Preferably, the microstructure and mechanical properties of the composite structure bioporous zinc alloy can be regulated by subsequent heat treatment.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] 1. Different from the prior art that prepares porous zinc alloys and then improves the biological activity of porous zinc alloys through surface modification, the present invention is based on laser additive manufacturing and vacuum-gas phase dealloying process to obtain a biological porous zinc alloy with a macro-micro dual-scale composite pore structure. While meeting the mechanical properties and modulus regulation of the porous zinc alloy, it effectively improves the biological activity of the porous zinc alloy, well promotes the adhesion, growth and differentiation of bone cells, and is suitable for orthopedic implant materials.

[0026] 2. Different from the prior art in which the biological coating added on the surface of porous zinc has poor bonding with the substrate, the macro-micro dual-scale composite pore structure in the porous zinc alloy prepared by the present invention is an integral structure, and there is no interface between the two, thus avoiding the problem of poor bonding between the biological coating and the substrate.

[0027] 3. Compared with powder metallurgy and traditional casting technology, the present invention is based on laser additive manufacturing, low-temperature sintering, and vacuum-gas phase dealloying processes. By adjusting the laser additive manufacturing process to adjust the macroscopic pore structure, the porous zinc alloy obtains a modulus matching that of bone tissue, better pore connectivity, and realizes regulation of the degradation rate. By adjusting the sintering time and temperature, that is, firstly low-temperature sintering is performed to promote the mutual diffusion between Zn and other metal elements such as Ti, and promote the formation of a second phase with a smaller size and different morphology, and then air-gas phase dealloying is performed to remove the second phase to form different pore morphologies, and obtain a microporous structure, thereby adjusting the micro-nanoporous structure, effectively improving the biological activity of the porous zinc alloy, promoting the adhesion, proliferation and differentiation of osteoblasts, and realizing the personalized pore structure optimization design and preparation, to meet the diverse needs of orthopedic clinical implants to the greatest extent.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a flow chart of the preparation process of the composite structure biological porous zinc alloy.

[0030] Figure 2The porous Zn with macroscopic pore structure prepared in Example 1 of the present invention 30 Ti 70 Macroscopic morphology of the alloy.

[0031] Figure 3 The composite structure biological porous Zn prepared in Example 1 of the present invention 30 Ti 70 Microscopic morphology of the alloy. DETAILED DESCRIPTION

[0032] Example 1

[0033] like Figure 1 As shown, this embodiment includes the following steps:

[0034] Step 1: Select 3D printed spherical zinc powder and titanium powder with a particle size of 15 μm to 53 μm, and mix them mechanically in a double-shaft horizontal mixer in a mass ratio of 30:70. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;

[0035] Step 2: Based on the design criteria of bone implants, the macroscopic pore structure is optimized by using computer modeling software CAD to establish a G-structure porous zinc alloy model in the TPMS structure. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 90%;

[0036] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 30 Ti 70 alloy, height 15mm, diameter 10mm, such as Figure 2 The parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 80 W, scanning speed 400 mm / s, and the scanning strategy is strip mode;

[0037] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 30 Ti 70 The alloy was subjected to low temperature sintering and high temperature-gas phase dealloying treatment, and then taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a composite structure bioporous Zn 30 Ti 70 Alloy, its microstructure is as Figure 3As shown; the temperature of the low-temperature sintering is 300°C and the time is 30min; the temperature of the high-temperature-gas phase dealloying is 650°C, the vacuum degree is 5.5Pa, and the time is 1h.

[0038] The titanium powder in step 1 of this embodiment can also be replaced by iron powder.

[0039] Example 2

[0040] like Figure 1 As shown, this embodiment includes the following steps:

[0041] Step 1: Select 3D printed spherical zinc powder and titanium powder with a particle size of 15 μm to 53 μm, and mix them mechanically in a double-shaft horizontal mixer at a mass ratio of 70:30. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;

[0042] Step 2: Based on the design criteria of bone implants, computer modeling software CAD is used to optimize the macroscopic pore structure, and a body-centered cubic structure porous zinc alloy model is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 75%;

[0043] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 70 Ti 30 alloy, with a height of 15 mm and a diameter of 10 mm; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 60 W, scanning speed 200 mm / s, and the scanning strategy is strip mode;

[0044] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 70 Ti 30 The alloy was subjected to low temperature sintering and high temperature-gas phase dealloying treatment, and then taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a composite structure bioporous Zn 70 Ti 30 alloy; the low temperature sintering temperature is 250 ℃, the time is 30min; the high temperature - gas phase dealloying temperature is 550 ℃, the vacuum degree is 5.5Pa, and the time is 2h.

[0045] The titanium powder in step 1 of this embodiment can also be replaced by iron powder.

[0046] Example 3

[0047] like Figure 1As shown, this embodiment includes the following steps:

[0048] Step 1: Select 3D printed spherical zinc powder with a particle size of 15 μm to 53 μm and iron powder in a mass ratio of 50:50, and mechanically mix them on a double-shaft horizontal mixer. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;

[0049] Step 2: Based on the design criteria of bone implants, computer modeling software CAD is used to optimize the macroscopic pore structure, and a porous zinc alloy model with a negative Poisson's ratio structure is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 60%;

[0050] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 50 Ti 50 alloy, with a height of 15 mm and a diameter of 10 mm; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 120 W, scanning speed 800 mm / s, and the scanning strategy is strip mode;

[0051] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 50 Ti 50 The alloy was subjected to low temperature sintering and high temperature-gas phase dealloying treatment, and then taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a composite structure bioporous Zn 50 Ti 50 alloy; the low temperature sintering temperature is 280°C and the time is 30min; the high temperature - gas phase dealloying temperature is 450°C, the vacuum degree is 5.5Pa and the time is 3h.

[0052] The titanium powder in step 1 of this embodiment can also be replaced by iron powder.

[0053] Example 4

[0054] like Figure 1 As shown, this embodiment includes the following steps:

[0055] Step 1: Select 3D printed spherical zinc powder and titanium powder with a particle size of 15 μm to 53 μm, and mix them mechanically in a double-shaft horizontal mixer in a mass ratio of 50:70. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;

[0056] Step 2: Based on the design criteria of bone implants, the macroscopic pore structure is optimized by using computer modeling software CAD to establish a G-structure porous zinc alloy model in the TPMS structure. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 90%;

[0057] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 50 Ti 50 alloy, with a height of 15 mm and a diameter of 10 mm; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 120 W, scanning speed 600 mm / s, and the scanning strategy is strip mode;

[0058] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 50 Ti 50 The alloy was subjected to low temperature sintering and high temperature-gas phase dealloying treatment, and then taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a composite structure bioporous Zn 50 Ti 50 alloy; the low temperature sintering temperature is 300°C and the time is 30min; the high temperature - gas phase dealloying temperature is 650°C, the vacuum degree is 5.5Pa and the time is 1h.

[0059] The titanium powder in step 1 of this embodiment can also be replaced by iron powder.

[0060] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a composite structure bioporous zinc alloy for orthopedic implants, characterized in that: First, the pore structure is optimized and designed by computer. According to the modeling results, a porous zinc alloy with a macroscopic pore structure is prepared by laser selective melting process. Then, a vacuum-vapor phase dealloying process is used to prepare a micro-nano pore structure to obtain a composite structure biological porous zinc alloy.

2. The method for preparing a composite structure bioporous zinc alloy for orthopedic implant according to claim 1, characterized in that: The computer pore structure optimization design modeling is performed based on the design criteria of the bone implant.

3. The method for preparing a bioporous zinc alloy for orthopedic implant composite structure according to claim 1, characterized in that: The raw material powder used in the laser selective melting process is spherical powder for 3D printing, with a particle size of 15 μm to 53 μm, and the raw material powder is mechanically mixed under a vacuum state.

4. The method for preparing a composite structure bioporous zinc alloy for orthopedic implant according to claim 1, characterized in that: The parameters of the laser selective melting process are: laser power 60W-120W, scanning speed 200mm / s-800mm / s, and scanning strategy is strip mode.

5. The method for preparing a bioporous zinc alloy for orthopedic implant composite structure according to claim 1, characterized in that: The parameters of the vacuum-gas phase dealloying process are: vacuum degree less than 10 Pa, dealloying temperature 450° C. to 650° C., and dealloying time 1 h to 3 h.

6. The method for preparing a bioporous zinc alloy for orthopedic implant composite structure according to claim 1, characterized in that: The method comprises the following steps: Step 1: Select 3D printed spherical zinc powder and titanium powder or iron powder in a mass ratio of 30-70:70-30 and mechanically mix them on a double-shaft horizontal mixer. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder; Step 2: Based on the design criteria of bone implants, computer modeling software is used to optimize the macroscopic pore structure, and a porous zinc alloy model of TPMS, body-centered cubic or negative Poisson's ratio structure is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 60% to 90%; Step 3: Using the mixed powder obtained in step 1 as a raw material, according to the modeling result in step 2, a porous zinc alloy with a macroscopic pore structure is prepared by a laser selective melting process; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 60W-120W, scanning speed 200mm / s-800mm / s, and the scanning strategy is strip mode; Step 4: subjecting the porous zinc alloy with a macroporous structure prepared in step 3 to low-temperature sintering and high-temperature-gas phase dealloying treatment, taking it out after cooling in the furnace, ultrasonically cleaning it with anhydrous ethanol for 30 minutes and then drying it to obtain a composite structure biological porous zinc alloy; the temperature of the low-temperature sintering is 250°C to 300°C, and the time is 30 minutes; the temperature of the high-temperature-gas phase dealloying is 450°C to 650°C, the vacuum degree is 5.5Pa, and the time is 1h to 3h.

7. The method for preparing a composite structure bioporous zinc alloy for orthopedic implant according to claim 6, characterized in that: The parameters of the laser selective melting process in step 3 are: laser power 80W, scanning speed 400mm / s, or laser power 120W, scanning speed 600mm / s.

8. The method for preparing a bioporous zinc alloy for orthopedic implant composite structure according to claim 6, characterized in that: The temperature of the low-temperature sintering in step 4 is 300° C. and the time is 30 minutes; the temperature of the high-temperature-gas phase dealloying is 550° C. and the time is 2 hours.

9. The method for preparing a bioporous zinc alloy with a composite structure for orthopedic implants according to claim 6, characterized in that: The composite structure bioporous zinc alloy described in step 4 has both micro-macro pore structure characteristics.

Citation Information

Patent Citations

  • Preparation method of multihole zinc magnesium alloy / hydroxyapatite composite material

    CN107855528A

  • Preparation method of porous zinc-silver alloy biological scaffold material

    CN108977682A

  • Porous zinc and preparation and application thereof

    CN109811396A

  • Biodegradable double-size macro-micro porous zinc scaffold for bone repair and preparation method of biodegradable double-size macro-micro porous zinc scaffold

    CN113770352A

  • TPMS structure-based zinc alloy or composite material tissue engineering scaffold thereof and preparation thereof

    CN115671380A